The scent of stress: Pintado catfish differentially respond to chemical cues from stressed conspecifics - Giaquinto, Percilia C. [UNESP]; Hoffmann, Anette (Brill Academic Publishers, 2012)
We examined whether pintado catfish (Pseudoplatystoma corruscans) can discriminate between scents of non-injured conspecifics stressed by a predator or by confinement and how fish use this information in the trade-off between feeding and predator avoidance. In the confinement stress condition, fish ingested the food, whereas in the predator stress condition, fish did not eat. This finding and comparisons of the latency to food ingestion and the time spent swimming between the confinement and predator-stress conditions indicated that pintado catfish can discriminate between conspecifics stressed by a predator or confinement using chemical cues, and use this information for adjusting the trade-off between food intake and predator avoidance.
Keywords: chemical cues; stress; antipredator behavior; predator avoidance; feeding behavior; catfish; Pseudoplatystoma corruscans